Performance evaluation of solar PV module with filters in an outdoor environment - Ramkiran, B.; Sundarabalan, C. K.; Sudhakar, K. (Elsevier, 2020)
Energy is the current need of the hour. Energy shortage in every part of the world has lead to the need for exploration of renewable sources of energy. Solar energy is the most prominently used renewable form of energy. Solar photovoltaic system efficiency depends on the wavelength of the solar radiation it is exposed to. In the present study, extensive research has been carried using different colour filter papers to evaluate the electrical performance of the solar photovoltaic module. Five different filters were used from magenta to red so that the relationship of frequency or wavelength and photonic energy can be determined. The efficiency and power of the solar photovoltaic module were measured with and without filters, and their performance was compared. From the study, it has been concluded that among all the colour filters used, magenta colour in the visible spectrum of solar radiation gave the maximum efficiency. The results also show that blue and magenta have maximum scope for producing more change in temperature when compared to other filters. The standard deviation is more in the case of these two filters, and all the filters have better standard deviation when compared without a filter.